Proceedings of the 24th International Conference on World Wide Web 2015
DOI: 10.1145/2740908.2742469
|View full text |Cite
|
Sign up to set email alerts
|

This is your Twitter on drugs

Abstract: Twitter can be a rich source of information when one wants to monitor trends related to a given topic. In this paper, we look at how tweets can augment a public health program that studies emerging patterns of illicit drug use. We describe the architecture necessary to collect vast numbers of tweets over time based on a large number of search terms and the challenges that come with finding relevant information in the collected tweets. We then show several examples of early analysis we have done on this data, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…He and Rothschild examine different methods of obtaining relevant political tweets, establishing that bias exists in keywordbased data collection (He and Rothschild, 2016) affecting both the users included in the sample as well as the sentiment of the resultant tweets. Predicting Influenza rates from search queries (Yuan et al, 2013) Understanding the use and effect of psychiatric drugs through Twitter (Buntain and Golbeck, 2015) Attribute Using attributes such as location or community affiliation to subset entities such as users who may have the relevant attribute in their biography…”
Section: Data Collectionmentioning
confidence: 99%
“…He and Rothschild examine different methods of obtaining relevant political tweets, establishing that bias exists in keywordbased data collection (He and Rothschild, 2016) affecting both the users included in the sample as well as the sentiment of the resultant tweets. Predicting Influenza rates from search queries (Yuan et al, 2013) Understanding the use and effect of psychiatric drugs through Twitter (Buntain and Golbeck, 2015) Attribute Using attributes such as location or community affiliation to subset entities such as users who may have the relevant attribute in their biography…”
Section: Data Collectionmentioning
confidence: 99%
“…Studies have suggested that social media posts mentioning opioids and other abuse-prone substances contain detectable signals of abuse or misuse, [20][21][22] with some users openly sharing such information, which they may not share with their physicians or through any other means. 13,17,23,24 Manual analyses established the potential of social media for drug abuse research, but automated, data-centric processing pipelines are required to fully realize social media's research potential. However, the characteristics of social media data present numerous challenges to automatic processing from the perspective of natural language processing and machine learning, including the presence of misspellings, colloquial expressions, data imbalance, and noise.…”
Section: Introductionmentioning
confidence: 99%
“…First, Twitter has been the subject of numerous studies. For instance, Buntain et al [9] studied emerging patterns of illicit drug use by analyzing tweets. They geolocated the tweets and categorized them based on tracking the frequency of drug names over time.…”
Section: Drug Abuse Detectionmentioning
confidence: 99%